ACADEMIC ACHIEVEMENT OF STUDENTS WITH INTELLECTUAL DISABILITIES IN RELATION TO PHYSICAL FITNESS AND LEARNING MOTIVATION - Sya'bani Rahman; Ngadiman -; Rohman Hidayat; Neva Widanita; Ayu Rizky Febriani (Riyadhoh: Jurnal Pendidikan Olahraga)
This study investigates the relationship between physical fitness, learning motivation, and academic achievement in students with intellectual disabilities at SLB Tamanwinangun. Using a quantitative, cross-sectional design, 21 students were selected through purposive sampling. Data analysis involved Pearson and multiple correlation tests. Results revealed a significant correlation between physical fitness and academic achievement (p = 0.008, r = 0.560), as well as between learning motivation and academic achievement (p = 0.000, r = 0.741). Additionally, a combined influence of both physical fitness and learning motivation on academic performance was found to be significant (p = 0.000). In conclusion, both physical fitness and learning motivation play a crucial role in supporting academic success among students with intellectual disabilities.